1989
DOI: 10.1128/mcb.9.2.787
|View full text |Cite
|
Sign up to set email alerts
|

Structure, chromosome location, and expression of the mouse zinc finger gene Krox-20: multiple gene products and coregulation with the proto-oncogene c-fos.

Abstract: We have analyzed the structure and the regulation of Krox-20, a mouse zinc finger-encoding gene which is transiently activated following serum stimulation of quiescent fibroblast cells in culture. The gene is localized on chromosome 10, band B5, in the mouse, and the homologous human gene also maps to chromosome 10 (region q21.1 to q22.1). Alternative splicing of the 5'-most intron of the Krox-20 gene gives rise to mRNAs encoding putative zinc finger proteins with different N termini. The first exon contains a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(59 citation statements)
references
References 69 publications
1
58
0
Order By: Relevance
“…5 gene induced by LSD is krox-20, which encodes for a zinc finger transcription factor. Krox-20 contains a c-fos serum response element in its promoter region, suggesting that it is co-regulated with c-fos (Chavrier et al 1989). Krox-20 has been shown to be necessary for normal brain development (Seitanidou et al 1997) and may be involved in the maintenance of long-term potentiation (Inokuchi et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…5 gene induced by LSD is krox-20, which encodes for a zinc finger transcription factor. Krox-20 contains a c-fos serum response element in its promoter region, suggesting that it is co-regulated with c-fos (Chavrier et al 1989). Krox-20 has been shown to be necessary for normal brain development (Seitanidou et al 1997) and may be involved in the maintenance of long-term potentiation (Inokuchi et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these results provide a functional link between activation of ERKs and regulation of glutamateinduced neuronal gene expression. Because some glutamateregulated immediate early genes (IEGs) such as Zif268 and Krox 20 are also induced by LTP paradigms, and SREs are present within the promoters of these IEGs (Changelian et al, 1989;Chavrier et al, 1989;Christy and Nathans, 1989), the mechanisms described here for the regulation of c-fos SRE transcription may be used generally by neurons to regulate gene expression during LTP and other adaptive neuronal responses.…”
Section: Discussionmentioning
confidence: 99%
“…SRF was ®rst identi®ed based on its ability to mediate serum and growth factor activation of the c-fos proto-oncogene (reviewed in Treisman and Ammerer, 1992). Subsequently, it was found that SRF and/or SRF binding sites (CC(A/ T) 6 GG), termed CArG boxes, regulate expression of a wide variety of serum responsive genes (Changelian et al, 1989;Chavrier et al, 1989;Christy and Nathans, 1989;Latinkic et al, 1991;Latinkic and Lau, 1994;Treisman, 1990;Tsai-Morris et al, 1988). SRF also regulates transcription mediated by treatment of cells with neurotrophins (Sheng et al, 1988;Visvader et al, 1988), neurotransmitters and agents that raise intracellular calcium levels (Bading et al, 1993;McDonough et al, 1997;Misra et al, 1994), stress agents, and viral activators (Avantaggiati et al, 1993;Fujii et al, 1992Fujii et al, , 1994.…”
Section: Introductionmentioning
confidence: 99%